West's federal taxation. Corporations, partnerships, estates & trusts - William H. Hoffman; Jr. (Thomson/South-Western, 2008)
The book gives strong emphasis to the importance of careful tax planning with special sections and integrated tax planning applications and suggestions throughout most chapters. It also offers solid coverage of how taxation is affected by international concerns. Preparing you for the long term, WFT offers readers many opportunities to sharpen critical-thinking and writing skills as well as build upon your knowledge as you progress through the text with unique features like the Multi-Issue Problems. In addition, Internet exercises are tied directly to chapter research cases, giving you valuable hands-on experience using online resources to solve real tax issues. Packed with examples, practical applications, and powerful learning tools, WEST FEDERAL TAXATION: CORPORATIONS, PARTNERSHIPS, ESTATES & TRUSTS, 2008 EDITION delivers the most comprehensive coverage available